Nano anticorrosive paint and application thereof

By adding modified hexagonal boron nitride and laminated structure zinc-aluminum alloy powder to the epoxy resin coating, the nano-anti-corrosion coating is formed, which solves the problem of insufficient anti-corrosion performance of the existing coating in corrosive environments, and significantly improves the anti-corrosion performance and adhesion of the coating.

CN119912858APending Publication Date: 2025-05-02CHINACOAL BEIJING COAL MINING MACHINERY CO LTD

Patent Information

Application Number
CN202510211276.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing epoxy resin coatings cannot provide long-term effective anti-corrosion protection, especially in highly corrosive industrial environments such as acid and alkali.

Method used

A nano-anti-corrosion coating was developed, and a composite coating was formed by adding bisphenol A-type epoxy resin, modified hexagonal boron nitride nanosheets and laminated structure zinc-aluminum alloy powder to component A, and adding polyamide curing agent to component B to form a composite coating to improve corrosion resistance.

Benefits of technology

It significantly improves the impedance mode value of the coating, reduces the corrosion current density, enhances the corrosion resistance of the coating, improves salt spray resistance, toughness, hardness and wear resistance, and improves the adhesion between the coating and the metal matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a nano anticorrosive coating. The invention provides a nano anticorrosive coating which comprises a component A and a component B. The component A comprises 40-100 parts by weight of bisphenol A epoxy resin, 0.3-5 parts by weight of cerium dioxide modified hexagonal boron nitride nanosheets and 60-85 parts by weight of lamellar structure zinc-aluminum alloy powder. And the component B comprises 20-40 parts of a polyamide curing agent. The zinc-aluminum alloy particles can enhance the toughness of the coating, and the cerium dioxide and hexagonal boron nitride are added to improve the hardness and wear resistance of the coating. And cerium dioxide and hexagonal boron nitride are added, so that the impedance modulus value of the coating is remarkably improved, the corrosion current density is reduced, and the corrosion resistance of the coating is enhanced. In a salt spray test, the modified coating shows better salt spray resistance, and a coating stripping area is not expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, in particular to nano anti-corrosion coatings and applications thereof. Background Art

[0002] In modern industry and infrastructure construction, materials such as metal, wood, and concrete are exposed to the natural environment or special industrial environment for a long time, and are extremely vulnerable to the threat of corrosion. Take metal as an example. Whether it is bridges, ships, building steel structures, or oil pipelines, chemical equipment, etc., corrosion will not only lead to a decrease in material strength and structural damage, shorten the service life, but also cause safety accidents and cause huge economic losses. According to relevant statistics, the direct economic losses caused by corrosion in the world are as high as trillions of dollars each year. Although the existing anti-corrosion coatings can alleviate the problem of material corrosion to a certain extent, they are obviously insufficient: some coatings have weak resistance to chemical media erosion and are difficult to provide lasting protection in highly corrosive industrial environments such as acids and alkalis. Therefore, in the field of anti-corrosion systems, improving the service life of metals is of great practical significance.

[0003] Among many coatings, organic coatings have become an important means of protecting metals from corrosion due to their directness and economy. Epoxy resin, as one of the commonly used organic coatings, is widely used in metal surface protection. It has many advantages, such as excellent mechanical properties, thermal stability, long service life, resistance to thermal stress, and strong adhesion to a variety of substrates. However, due to its high permeability, epoxy resin coatings cannot provide long-term and effective anti-corrosion protection. By adding suitable materials to the coating matrix to prepare a composite coating, the anti-corrosion ability of the coating can be significantly improved, making up for the shortcomings of epoxy resin coatings. In order to better solve the problem of material corrosion and meet the needs of industrial development for efficient, environmentally friendly, and high-performance anti-corrosion coatings, the development of new anti-corrosion coatings is imminent. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a nano anti-corrosion coating, which solves the technical problem that epoxy resin coating cannot provide long-term and effective anti-corrosion protection.

[0006] (II) Technical solution

[0007] In the first aspect, the present invention provides a nano anti-corrosion coating, comprising: a component A and a component B, wherein, by weight, the component A comprises 40-100 parts of bisphenol A epoxy resin, 0.3-5 parts of cerium dioxide modified hexagonal boron nitride nanosheets, and 60-85 parts of layered zinc-aluminum alloy powder; the component B comprises 20-40 parts of a polyamide curing agent.

[0008] Optionally, the component A further comprises 20-40 parts of a diluent and 1-8 parts of a defoaming agent.

[0009] Optionally, the bisphenol A epoxy resin is at least one of bisphenol A epoxy resin 128 and E51;

[0010] The polyamide curing agent is polyamide curing agent 651;

[0011] The diluent is at least one of toluene, xylene, ethyl acetate, n-butanol, and butyl glycidyl ether;

[0012] The defoaming agent is at least one of defoaming agent A530 and defoaming agent 088.

[0013] Optionally, component A includes 60-80 parts of bisphenol A epoxy resin, 1-4 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 70-80 parts of lamellar structure zinc aluminum alloy powder, 25-35 parts of diluent and 2-6 parts of defoaming agent;

[0014] Component B includes 25-35 parts of polyamide curing agent.

[0015] Optionally, component A includes 70 parts of bisphenol A epoxy resin, 3 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 78 parts of lamellar zinc aluminum alloy powder, 30 parts of diluent, and 5 parts of defoaming agent;

[0016] Component B includes 30 parts of polyamide curing agent.

[0017] Optionally, the preparation method of the cerium dioxide modified hexagonal boron nitride nanosheets is:

[0018] First, h-BN was dispersed in Tris buffer and ultrasonically treated, then dopamine hydrochloride was added, stirred and ultrasonicated, and then the mixed solution was heated and stirred in a 60°C water bath, then filtered on polyvinylidene fluoride filter paper and washed several times with anhydrous ethanol and deionized water, and dried to obtain a PDA-hBN complex;

[0019] Subsequently, the PDA-hBN complex was dispersed in an ethanol solution, and an aqueous cerium nitrate solution was added dropwise, stirred to fully mix, and then the pH was adjusted to 10, flocs were generated in the solution, stirred, and then filtered again, washed, and dried to obtain cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce.

[0020] Optionally, the preparation method of the nano anti-corrosion coating is as follows: add bisphenol A type epoxy resin and a diluent into a container, stir to dissolve, and form a base material; add cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce to the base material, add layered zinc-aluminum alloy powder in batches, shear and disperse to ensure that the filler is evenly distributed; add a defoaming agent to eliminate bubbles to obtain the component A; the filler refers to cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and layered zinc-aluminum alloy powder.

[0021] In a second aspect, the nano anti-corrosion coating according to the first aspect of the present invention is used in marine equipment.

[0022] Optionally, before use, the component A and the component B are mixed evenly, applied to the surface of the marine equipment, and cured.

[0023] (III) Beneficial effects

[0024] Electrochemical tests show that the addition of cerium dioxide and hexagonal boron nitride significantly increases the impedance modulus of the coating and reduces the corrosion current density, thereby enhancing the anti-corrosion performance of the coating. In the salt spray test, the modified coating exhibits better salt spray resistance, and the coating peeling area does not expand.

[0025] Zinc-aluminum alloy particles can enhance the toughness of the coating, while the addition of cerium dioxide and hexagonal boron nitride can improve the hardness and wear resistance of the coating. The addition of hexagonal boron nitride and zinc-aluminum alloy can improve the adhesion between the epoxy resin coating and the metal substrate. Good adhesion helps the coating form a uniform and dense protective layer on the metal surface, reducing the micropores and microcracks between the coating and the substrate, thereby improving the anti-corrosion performance of the coating. This comprehensive improvement in mechanical properties helps the coating maintain its integrity in complex use environments and reduces anti-corrosion failure caused by mechanical damage.

[0026] Hexagonal boron nitride has good thermal conductivity. Its addition can improve the thermal conductivity of the coating, help to quickly conduct heat in a high temperature environment, and avoid accelerated coating aging and corrosion caused by local overheating. DETAILED DESCRIPTION

[0027] In order to better explain the present invention and facilitate understanding, the present invention is described in detail through specific implementation methods.

[0028] Hexagonal boron nitride h-BN has good mechanical properties, high thermal conductivity, high impermeability and electrical insulation properties, so it has attracted much attention. Studies have found that due to the lamellar structure and wide bandgap semiconductor properties of h-BN, excellent corrosion resistance can be obtained when h-BN is used as a polymer filler. In addition, hexagonal boron nitride has good compatibility with epoxy resin and can be evenly dispersed in the epoxy resin matrix. On the one hand, the high hardness and high strength characteristics of hexagonal boron nitride give the coating better mechanical properties; on the other hand, during the curing process, the presence of hexagonal boron nitride prompts the epoxy resin to form a denser cross-linked network structure. This synergistic effect not only enhances the cohesion of the coating and improves the overall strength of the coating, but also improves the flexibility and impact resistance of the coating, making it less likely to be damaged when subjected to external forces, thereby ensuring the anti-corrosion performance of the coating.

[0029] In practical application scenarios, the use of h-BN in epoxy-based coatings has certain limitations. On the one hand, the difference in electronegativity between B and N causes a "lip-lip" interaction between adjacent layers, which makes it difficult to peel off a large amount of h-BN and very easy to re-agglomerate. On the other hand, h-BN has strong chemical stability and lacks surface active groups, which greatly increases the difficulty of covalent modification and makes it difficult to improve its dispersibility in epoxy coatings. Compared with covalent modification, methods based on non-covalent modification are more feasible. This is because the coupling agent can be physically adsorbed on the h-BN surface, which is not only conducive to subsequent further modification, but also maintains the structure and properties of h-BN. Among the many non-covalent modification methods, dopamine-modified h-BN is widely used to improve interfacial adhesion.

[0030] Furthermore, metal oxides or their salts can react chemically with the surface of hexagonal boron nitride, or attach to the surface of hexagonal boron nitride through physical adsorption, etc., to change the properties of the surface of hexagonal boron nitride. Taking cerium dioxide as an example, the hydrolysis reaction of cerium nitrate in an alkaline environment can be used to compound it onto hexagonal boron nitride. The prepared composite filler can be added to the coating to improve the corrosion resistance and other properties of the coating.

[0031] The anti-corrosion coating prepared by using cerium dioxide modified hexagonal boron nitride nanosheets has excellent functions. The principle is as follows:

[0032] Cerium dioxide has a special electronic structure. During the corrosion process, it can use its own redox properties to effectively capture free radicals generated in the corrosion reaction. Free radicals are key active intermediates in corrosion reactions. Cerium dioxide reacts with free radicals and converts them into relatively stable substances, thereby inhibiting the chain transfer of redox reactions and slowing down the corrosion process of the material.

[0033] Cerium dioxide has good antioxidant properties and can form a dense oxide film on the surface of the coating, effectively blocking the penetration of oxygen and moisture. In a corrosive environment, cerium dioxide can react with the corrosive medium to generate stable oxides, thereby repairing tiny defects in the coating. The nanostructure of cerium dioxide and hexagonal boron nitride can fill the micropores and microcracks in the epoxy resin coating, improving the density and adhesion of the coating.

[0034] Epoxy resin itself has the advantages of strong adhesion and small curing shrinkage. As the base film-forming material of the coating, it can form a strong chemical bond or physical adsorption with the surface of the protected material to ensure that the coating is tightly attached to the surface of the material. The modified hexagonal boron nitride has a unique lamellar structure. When it is dispersed in the epoxy resin matrix to form a coating, these lamellar layers will intertwine and overlap with each other to form a maze-like physical shielding layer. This structure can greatly extend the diffusion path of corrosive media (such as moisture, oxygen, acid and alkali ions, etc.) to the surface of the protected material, making it difficult for them to directly contact and corrode the material, thereby effectively preventing the occurrence of corrosion. In this way, the molecular structure of the epoxy resin is optimized, and the cross-linked network formed during the curing process is more dense and stable, which further enhances the adhesion of the coating to the protected material, and at the same time builds a solid protective barrier to effectively block the invasion of external corrosive substances.

[0035] The anti-corrosion coating obtained by composite modified epoxy resin of zinc-aluminum alloy has the following anti-corrosion principle:

[0036] Zn-Al alloy presents a unique layered composite structure in the composite coating, and its microstructure is composed of parallel stacked lamellar metal phases. This directional arrangement structure can significantly extend the diffusion path of the corrosive medium, and effectively improve the densification degree and anti-medium penetration performance of the coating through the physical barrier effect. From the analysis of the electrochemical protection mechanism, the Zn element in the alloy preferentially corrodes to form a sacrificial anode effect, and the dense corrosion products (mainly basic zinc carbonate) generated can fill the microporous structure in the coating and block the corrosion channel; while the Al element inhibits the depth extension of corrosion through the formation of a passivation film. The synergistic effect of the two reduces the corrosion rate of the composite coating by about 40-60% compared with the traditional coating. Experimental studies have shown that this metal phase composite protection mechanism not only effectively delays the initial corrosion of the base metal, but also maintains the long-term protective performance of the coating through the self-sealing effect of the product.

[0037] Example 1

[0038] The present embodiment provides a nano anticorrosive coating, comprising two components A and B, wherein the component A comprises the following raw materials in parts by weight: 40 parts of bisphenol A epoxy resin 128, 0.3 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 60 parts of lamellar zinc aluminum alloy powder, 20 parts of xylene, and 1 part of defoaming agent A530;

[0039] Component B includes the following raw materials in parts by weight: 20 parts of polyamide curing agent 651.

[0040] The preparation method of the cerium dioxide modified hexagonal boron nitride nanosheets is:

[0041] Hexagonal boron nitride (h-BN) pretreatment: h-BN was dispersed in Tris buffer with a concentration of 1×10 -5 mol / L, adjust the pH to 8.5 with dilute HCl solution, and ultrasonicate for 1-2h to fully disperse h-BN in the buffer.

[0042] Preparation of polydopamine-modified hexagonal boron nitride (PDA-hBN): add dopamine hydrochloride to the above solution, the mass ratio of h-BN to dopamine hydrochloride is 1:1, stir and ultrasonicate for 1-2 hours, heat and stir the mixed solution in a 60°C water bath for about 5 hours, then filter on polyvinylidene fluoride filter paper, wash several times with anhydrous ethanol and deionized water, and dry at 60°C for 24 hours to obtain a PDA-hBN complex.

[0043] Preparation of cerium dioxide modified hexagonal boron nitride nanosheets (PDA-hBN-Ce): PDA-hBN complex was dispersed in ethanol solution, cerium nitrate aqueous solution was added dropwise, the molar ratio of PDA-HBN to Ce(NO3)3 was 1:1, stirred for 0.5h to fully mix, and then the pH was adjusted to 10 with NaOH solution. Floccules will appear in the solution, stirred for 1h, and then filtered again, washed, and dried to obtain PDA-hBN-Ce complex, i.e., cerium dioxide modified hexagonal boron nitride.

[0044] The preparation method of the nano anticorrosive coating:

[0045] Add bisphenol A epoxy resin 128 and xylene to the reaction kettle, stir at a low speed of 300-500rpm for 10 minutes to fully dissolve the resin and form a uniform base material; slowly add cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce to the base material, start the high-speed disperser (1200-1500rpm), disperse for 30 minutes, and add a dispersant (such as BYK-110) if necessary to improve the dispersibility of the nanomaterial; add lamellar zinc-aluminum alloy powder in batches to avoid agglomeration, switch to high-speed shear dispersion (2000rpm) for 40 minutes to ensure uniform distribution of the filler; add defoamer A530, stir at a low speed of 500rpm for 10 minutes, let stand for 15 minutes to eliminate bubbles; finally add polyamide curing agent 651, stir, and vacuum degas at room temperature; cure at room temperature for 24 hours, or bake at 80℃ for 2 hours to accelerate curing.

[0046] Example 2

[0047] The present embodiment provides a nano anticorrosive coating, comprising two components A and B, wherein the component A comprises the following raw materials in parts by weight: 100 parts of bisphenol A epoxy resin E51, 5 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 85 parts of lamellar zinc aluminum alloy powder, 40 parts of toluene, and 8 parts of defoaming agent 088;

[0048] Component B includes the following raw materials in parts by weight: 40 parts of polyamide curing agent 651.

[0049] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0050] Example 3

[0051] The present embodiment provides a nano anticorrosive coating, comprising two components A and B, wherein the component A comprises the following raw materials in parts by weight: 60 parts of bisphenol A epoxy resin 128, 1 part of cerium dioxide modified hexagonal boron nitride nanosheets, 70 parts of lamellar zinc aluminum alloy powder, 25 parts of ethyl acetate, and 2 parts of defoaming agent A530;

[0052] Component B includes the following raw materials in parts by weight: 25 parts of polyamide curing agent 651.

[0053] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0054] Example 4

[0055] The present embodiment provides a nano anticorrosive coating, comprising two components A and B, wherein the component A comprises the following raw materials in parts by weight: 70 parts of bisphenol A epoxy resin E51, 3 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 78 parts of lamellar zinc aluminum alloy powder, 30 parts of diluent butyl glycidyl ether, and 5 parts of defoaming agent A530;

[0056] Component B includes the following raw materials in parts by weight: 30 parts of polyamide curing agent 651.

[0057] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0058] Example 5

[0059] The present embodiment provides a nano anticorrosive coating, comprising two components A and B, wherein the component A comprises the following raw materials in parts by weight: 128 80 parts of bisphenol A epoxy resin, 4 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 80 parts of lamellar structure zinc aluminum alloy powder, 35 parts of diluent ethyl acetate, and 6 parts of defoaming agent 088;

[0060] Component B includes the following raw materials in parts by weight: 35 parts of polyamide curing agent 651.

[0061] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0062] Comparative Example 1

[0063] A nano anti-corrosion coating provided in this embodiment includes two components, A and B. Component A includes the following raw materials in parts by weight: 70 parts of bisphenol A epoxy resin E51, 30 parts of diluent n-butanol, and 5 parts of defoamer A530; component B includes the following raw materials in parts by weight: 30 parts of polyamide curing agent 651.

[0064] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0065] Comparative Example 2

[0066] A nano anti-corrosion coating provided in this embodiment includes two components, A and B. Component A includes the following raw materials in parts by weight: 70 parts of bisphenol A epoxy resin E51, 3 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 30 parts of diluent n-butanol, and 5 parts of defoaming agent A530; component B includes the following raw materials in parts by weight: 30 parts of polyamide curing agent 651.

[0067] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0068] Comparative Example 3

[0069] A nano anti-corrosion coating provided in this embodiment includes two components, A and B. Component A includes the following raw materials in parts by weight: 70 parts of bisphenol A epoxy resin E51, 78 parts of lamellar zinc-aluminum alloy powder, 30 parts of diluent n-butanol, and 5 parts of defoaming agent A530; component B includes the following raw materials in parts by weight: 30 parts of polyamide curing agent 651.

[0070] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0071] Comparative Example 4

[0072] A nano anti-corrosion coating provided in this embodiment includes two components, A and B. Component A includes the following raw materials in parts by weight: 70 parts of bisphenol A epoxy resin E51, 3 parts of hexagonal boron nitride, 78 parts of lamellar zinc-aluminum alloy powder, 30 parts of diluent n-butanol, and 5 parts of defoaming agent A530; component B includes the following raw materials in parts by weight: 30 parts of polyamide curing agent 651.

[0073] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0074] Comparative Example 5

[0075] A nano anti-corrosion coating provided in this embodiment includes two components, A and B. Component A includes the following raw materials in parts by weight: 70 parts of bisphenol A epoxy resin E51, 3 parts of hexagonal boron nitride, 30 parts of diluent n-butanol, and 5 parts of defoamer A530; component B includes the following raw materials in parts by weight: 30 parts of polyamide curing agent 651.

[0076] The preparation methods of the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the nano anti-corrosion coating are the same as those in Example 1.

[0077] The coating of the present invention was tested for performance after being completely cured. The main performance index detection methods are shown in Table 1. The test results of Examples 1-5 of the present invention and Comparative Examples 1-5 are shown in Table 2. Unless otherwise specified, the test temperature is the natural temperature.

[0078] Table 1 Main performance indicators and detection methods used in the present invention

[0079]

[0080]

[0081] Table 2 Test results of Examples 1-5 of the present invention and Comparative Examples 1-5

[0082]

[0083]

[0084] In the test, “intact” is judged as “no blistering, no peeling, no rust and no cracking of the coating”.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nano anti-corrosion coating, characterized in that: include: It includes component A and component B. Wherein, by weight, the component A comprises 40-100 parts of bisphenol A epoxy resin, 0.3-5 parts of cerium dioxide modified hexagonal boron nitride nanosheets, and 60-85 parts of layered zinc-aluminum alloy powder; the component B comprises 20-40 parts of polyamide curing agent.

2. The nano anticorrosion coating according to claim 1, characterized in that: The component A also includes 20-40 parts of diluent and 1-8 parts of defoaming agent.

3. The nano anticorrosion coating according to claim 1 or 2, characterized in that: The bisphenol A epoxy resin is at least one of bisphenol A epoxy resin 128 and E51; The polyamide curing agent is polyamide curing agent 651; The diluent is at least one of toluene, xylene, ethyl acetate, n-butanol, and butyl glycidyl ether; The defoaming agent is at least one of defoaming agent A530 and defoaming agent 088.

4. The nano anticorrosion coating according to claim 3, characterized in that: Component A comprises 60-80 parts of bisphenol A epoxy resin, 1-4 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 70-80 parts of lamellar structure zinc-aluminum alloy powder, 25-35 parts of diluent and 2-6 parts of defoaming agent; Component B includes 25-35 parts of polyamide curing agent.

5. The nano anticorrosion coating according to claim 4, characterized in that: Component A includes 70 parts of bisphenol A epoxy resin, 3 parts of cerium dioxide modified hexagonal boron nitride nanosheets, 78 parts of lamellar zinc aluminum alloy powder, 30 parts of diluent, and 5 parts of defoaming agent; Component B includes 30 parts of polyamide curing agent.

6. The nano anticorrosion coating according to claim 5, characterized in that: The preparation method of the cerium dioxide modified hexagonal boron nitride nanosheets is: First, h-BN was dispersed in Tris buffer and ultrasonically treated, then dopamine hydrochloride was added, stirred and ultrasonicated, and then the mixed solution was heated and stirred in a 60°C water bath, then filtered on polyvinylidene fluoride filter paper and washed several times with anhydrous ethanol and deionized water, and dried to obtain a PDA-hBN complex; Subsequently, the PDA-hBN complex was dispersed in an ethanol solution, and an aqueous cerium nitrate solution was added dropwise, stirred to fully mix, and then the pH was adjusted to 10, flocs were generated in the solution, stirred, and then filtered again, washed, and dried to obtain cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce.

7. The nano anticorrosion coating according to claim 6, characterized in that: The preparation method of the nano anti-corrosion coating is as follows: bisphenol A type epoxy resin and a diluent are added into a container, stirred to dissolve, and a base material is formed; cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce are added into the base material, and lamellar zinc-aluminum alloy powder is added in batches, sheared and dispersed to ensure that the filler is evenly distributed; a defoaming agent is added to eliminate bubbles to obtain the component A; the filler refers to the cerium dioxide modified hexagonal boron nitride nanosheets PDA-hBN-Ce and the lamellar zinc-aluminum alloy powder.

8. Use of the nano anti-corrosion coating according to any one of claims 1 to 7 in marine equipment.

9. The use according to claim 8, characterized in that: Before use, the component A and the component B are mixed evenly, applied to the surface of the marine equipment, and cured.

Citation Information

Patent Citations

  • Nano-modified epoxy heavy-duty anti-corrosion coating

    CN111004557A

  • Preparation method of cerium dioxide modified hexagonal boron nitride reinforced epoxy coating on surface of NdFeB magnet

    CN117659814A

  • High-solid anticorrosive paint for use in steel structure surfaces, and spraying method therefor

    WO2019052070A1

Cited By

  • High-temperature-resistant and corrosion-resistant coating for aluminum alloy heat exchange tube and preparation method thereof

    CN121343472A